Supply Chain Management Agroindustri : Sebuah Literature Review - Dedet Deperiky; Santosa Santosa; Rika Ampuh Hadiguna; Nofialdi Nofialdi (Politeknik ATI Padang, 2020)
Agroindustry needs further attention from the relationship between supply chain actors to improve efficiency in terms of partnerships and the application of modern technology today. Supply chain management in agroindustry emphasizes a management approach to a network of facilities and distribution channels that includes procurement of materials, production, and delivery of agroindustry products to end consumers. The research methodology used is the Systematic Literature Review (SLR) method, which is the literature review method that identifies, evaluates, and interprets all findings on a research topic, to answer research questions. The results of the study imply that in order to manage the agroindustry supply chain the entire supply chain structure must be well understood by focusing more on the quality of external relations with supply chain actors and who focus actor on partnership, trust and sustainability in conducting agroindustry supply chain activities. Agroindustry managers must investigate why they must manage, what must be managed and how to manage agroindustry supply chains. To explore the agroindustry supply chain that a manager must integrated the system, examine the nature, linkages and dependencies between business operations in the agroindustry supply chain. Suggestions from researchers that this four-step approach to meeting sustainability must be implemented in the agroindustry supply chain, and optimalized or later all organizations will adopt the SCM concept in achieving competitive advantage.